2007
DOI: 10.1099/mic.0.2007/010371-0
|View full text |Cite
|
Sign up to set email alerts
|

Strain-specific proteome responses of Pseudomonas aeruginosa to biofilm-associated growth and to calcium

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that forms biofilms on mucous plugs in the lungs of cystic fibrosis (CF) patients, resulting in chronic infections. Pulmonary P. aeruginosa isolates often display a mucoid (alginate-producing) phenotype, whereas non-mucoid strains are generally associated with acute infections. We characterized the cytosolic proteomes of biofilm-associated and planktonic forms of a CF pulmonary isolate, P. aeruginosa FRD1, and a non-mucoid strain, PAO1. Since Ca 2+ metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 67 publications
3
76
2
2
Order By: Relevance
“…4) (see Table S3 in the supplemental material). Our previous proteomics study using whole biofilms showed high protein amounts of chaperones and proteases generally associated with the heat shock response (50). The transcriptomics results here are consistent with those of the proteomics study and also indicate that proteases and chaperones regulated by RpoH and misfolded protein stress are highly induced at the top of these biofilms.…”
Section: Fig 2 Microarray Results Of Mrna Signal Intensities Of Metabsupporting
confidence: 78%
See 2 more Smart Citations
“…4) (see Table S3 in the supplemental material). Our previous proteomics study using whole biofilms showed high protein amounts of chaperones and proteases generally associated with the heat shock response (50). The transcriptomics results here are consistent with those of the proteomics study and also indicate that proteases and chaperones regulated by RpoH and misfolded protein stress are highly induced at the top of these biofilms.…”
Section: Fig 2 Microarray Results Of Mrna Signal Intensities Of Metabsupporting
confidence: 78%
“…The two most abundant usp mRNA transcripts are the uspK (PA3309) and uspN (PA4352) genes. Proteomic analysis of whole biofilms showed that UspK and UspN were abundant in P. aeruginosa biofilms (50). The previous proteomics study comparing two different P. aeruginosa strains in a flow-through biofilm system demonstrated that uspK and uspN induction and stress response may be a general feature of P. aeruginosa biofilms.…”
Section: Fig 2 Microarray Results Of Mrna Signal Intensities Of Metabmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterioferritins whose expression levels vary as a function of environmental and intracellular iron levels have been identified in P. putida KT2440 (Chen et al, 2009). Similarly, bacterioferritins are highly expressed in biofilms of P. aeruginosa (Patrauchan et al, 2007), but they have not been identified as being upregulated under N-limited growth conditions. Fig.…”
Section: Mclpha Synthesis Occurs Only Under N Limitationmentioning
confidence: 97%
“…During some stages of biofilm development, as much as 50% of the proteome can be differentially produced compared with the same cells growing in planktonic culture (Patrauchan et al, 2007;Sauer et al, 2002).…”
Section: Discussion Dynamic Equilibrium Of Microbial Phenotype Composmentioning
confidence: 99%